2022
DOI: 10.1021/acsapm.2c01646
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonically Active Supramolecular Polymer–Metal–Organic Framework Hydrogel Nanocomposite for Localized Chemo-photothermal Therapy

Abstract: Hydrogels are a three-dimensional cross-linked network of hydrophilic polymers, extensively used for biomedical, biotechnological, and pharmaceutical applications. The functionality of hydrogels could be enhanced by synthesizing hydrogel nanocomposites that can both enable controlled release of drugs in a cancerous microenvironment and near-infrared-induced localized heat generation for combined chemo-photothermal therapy (chemo-PTT), a potent anticancer therapeutic approach. Herein, we developed a plasmonical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
(46 reference statements)
0
4
0
Order By: Relevance
“…If the G 0 and G 00 curves intersect as the strain increases, the strain value at the intersection point represents the critical strain value required to break the hydrogel network. 50,54 During the alternating low-high-low shear strain cycle, if G 0 and G 00 can recover to their original values several times in a short period, this proves that the MOGs have repeatable self-healing properties. 155,156 For example, Zeng and colleagues 150 applied 300% and 1% continuously alternating shear strain to a MOG made of a bisphosphonate-modified hyaluronic acid hydrogel matrix and MOF (Fig.…”
Section: Mechanical Property Analysismentioning
confidence: 80%
See 1 more Smart Citation
“…If the G 0 and G 00 curves intersect as the strain increases, the strain value at the intersection point represents the critical strain value required to break the hydrogel network. 50,54 During the alternating low-high-low shear strain cycle, if G 0 and G 00 can recover to their original values several times in a short period, this proves that the MOGs have repeatable self-healing properties. 155,156 For example, Zeng and colleagues 150 applied 300% and 1% continuously alternating shear strain to a MOG made of a bisphosphonate-modified hyaluronic acid hydrogel matrix and MOF (Fig.…”
Section: Mechanical Property Analysismentioning
confidence: 80%
“…In the MOGs formed by MOFs and polymers, the MOF nanoparticles are trapped in the spaces between the polymer gel chains. 12 A variety of natural polymers (such as chitosan, 42 soybean hull polysaccharides, 43,44 gelatin, 45,46 silk fibroin, 47 pectin, 48,49 sodium alginate, [50][51][52] and starch 53 ), and synthetic polymers (such as carboxymethyl chitosan, 54 gelatin methacrylate, 55,56 polyacrylamide, 57,58 polyvinyl alcohol, 59 poloxamer, 60 and carboxymethylcellulose 61 ) is often used as the gelation agent (Table 1). This review further divides the synthetic strategy of these MOGs into three categories including ''MOF-first'', 62 ''polymer-first'', and ''one-pot'' (Fig.…”
Section: Mogs Formed By Mofs and Polymersmentioning
confidence: 99%
“…Numerous studies have shown that TNBC is highly prone to recurrence and metastasis, so, its prognosis was worse than subtypes of BC, and the 5-year survival rate of TNBC patients with distant metastasis is only 11% (Kaur et al, 2023;Li et al, 2023;Lim et al, 2020). Presently, the American Joint Commission on Cancer (AJCC) staging guidelines have become the gold standard for evaluating tumor prognosis (Amin et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Administrations by solubility-enhancing techniques, longacting injectable formulations, or lipid-based carrier systems are some of the possible approaches to overcoming the adverse biopharmaceutical properties of the drug. Several approaches such as polymeric micelles, 9 amorphous solid dispersions, 10 cyclodextrin complexes, 11 nanofibers, 1 albumin-bound nanoparticles, 12 nanocrystals, 13 nanosponges, 14,15 lipid hybrid nanoparticles, 16 polymer-stabilized nanoparticles, 17 and PEGylated liposomes 18 have been attempted to enhance the pharmacokinetic and physicochemical properties of LTP and variously evaluated in vitro and in vivo. These works have attempted to improve the therapeutic effectiveness of LTP mostly by designing spatial-controlled release systems such as hyaluronic acid-coated LTP nanocrystals and surface functionalization to enhance blood circulation time.…”
Section: ■ Introductionmentioning
confidence: 99%